Mechanisms of antibiotic resistance in enterococci (2014)
Multidrug-resistant (MDR) enterococci are important nosocomial pathogens and a growing clinical challenge. These organisms have developed resistance to virtually all antimicrobials currently used in clinical practice using a diverse number of genetic strategies. Due to this ability to recruit antibiotic resistance determinants, MDR enterococci display a wide repertoire of antibiotic resistance mechanisms including modification of drug targets, inactivation of therapeutic agents, overexpression of efflux pumps and a sophisticated cell envelope adaptive response that promotes survival in the human host and the nosocomial environment. MDR enterococci are well adapted to survive in the gastrointestinal tract and can become the dominant flora under antibiotic pressure, predisposing the severely ill and immunocompromised patient to invasive infections. A thorough understanding of the mechanisms underlying antibiotic resistance in enterococci is the first step for devising strategies to control the spread of these organisms and potentially establish novel therapeutic approaches.